2016
DOI: 10.1021/acscatal.6b00713
|View full text |Cite
|
Sign up to set email alerts
|

Surface Proton Hopping and Fast-Kinetics Pathway of Water Oxidation on Co3O4 (001) Surface

Abstract: We propose a mechanism of water splitting on cobalt oxide surface with atomistic thermodynamic and kinetic details. The density-functional theory studies suggest that the oxidation process could proceed with several nonelectrochemical (spontaneous) intermediate steps, following the initial electrochemical hydroxyl-to-oxo conversion. More specifically, the single oxo sites CoIVO can hop (via surface proton/electron hopping) to form oxo pair CoIV(O)-O-CoIVO, which will undergo nucleophilic attack by a water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 49 publications
7
97
0
1
Order By: Relevance
“…It is also found that these reactions continue even after the end of the initial hydrogen transfer. [23,24,25]The same mechanism is observed in our simulations. A single H-transfer from the LAH reducing agent was able to initiate a continuous insertion of additional Al's that eventually lead to the growth of a larger aluminum complex.…”
Section: Introductionsupporting
confidence: 88%
“…It is also found that these reactions continue even after the end of the initial hydrogen transfer. [23,24,25]The same mechanism is observed in our simulations. A single H-transfer from the LAH reducing agent was able to initiate a continuous insertion of additional Al's that eventually lead to the growth of a larger aluminum complex.…”
Section: Introductionsupporting
confidence: 88%
“…This increase of the liquid electrolyte thickness results in an apparent decrease of the H 2 O ads and OH ads spectral components due to the exponential decay of the photoelectron intensity within the electrolyte layer ( Figure S1c). Fourth, and finally, we consider that the emergence of new spectral features could result from generation of highly oxidized Co 4+ centers under OER conditions, as reported in the literature on the basis of electrochemical and infrared spectroscopic data (32,37,65,66 (65)). At equilibrium conditions, a steady-state concentration of Co 4+ is present on the electrode surface and can be detected with different spectroscopic methods (32).…”
Section: Operando Spectroscopic Investigation Of the Biphasic Coo X Smentioning
confidence: 82%
“…To reveal the impact of active electron modulation on the catalytic process, the energy profiles of the reaction pathway were further calculated (Figures S16 and S17) . First of all, we can see the overpotential of Co 3 O 4 is 750 mV from Figure a, whereas the overpotential of Co 3 O 4 ‐Ov is 620 mV and that of the CoO/Co 3 O 4 further decreased to 300 mV.…”
Section: Discussionmentioning
confidence: 99%